2020
DOI: 10.14814/phy2.14629
|View full text |Cite
|
Sign up to set email alerts
|

Polysorbate 80‐induced leaky gut impairs skeletal muscle metabolism in mice

Abstract: Impaired intestinal permeability can induce systemic inflammation and metabolic disturbance. However, the effect of impaired intestinal permeability on metabolic function in the skeletal muscle is unknown. Dietary polysorbate 80 (PS80), a common emulsifier, has been shown to impair intestinal permeability in mice. Here, we investigated the effect of PS80‐induced intestinal permeability on glucose tolerance with metabolic signaling in the skeletal muscle. Male ICR mice were divided into control and PS80 groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…The challenge also produced small, transient increases in circulating bacterial endotoxin (LPS) and systemic inflammation (SAA). The data provide evidence that horses undergoing this common combined challenge may be at risk for developing persistent inflammatory consequences typical of LGS, including suboptimal performance, 1 immune dysfunction, 48 and gastrointestinal inflammation 49 . The model may be a useful tool in further studies on the role of alterations in gastrointestinal permeability in equine disease.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The challenge also produced small, transient increases in circulating bacterial endotoxin (LPS) and systemic inflammation (SAA). The data provide evidence that horses undergoing this common combined challenge may be at risk for developing persistent inflammatory consequences typical of LGS, including suboptimal performance, 1 immune dysfunction, 48 and gastrointestinal inflammation 49 . The model may be a useful tool in further studies on the role of alterations in gastrointestinal permeability in equine disease.…”
Section: Discussionmentioning
confidence: 90%
“…The resulting hyperpermeability (or ‘leakiness’) of the gastrointestinal tract can trigger aberrant systemic inflammatory responses. Clinical manifestations of these inflammatory responses, which may include impaired skeletal muscle metabolism, 1 metabolic dysfunction, 2,3 allergies, 4,5 and inflammatory diseases such as arthritis, 6 are collectively termed LGS.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, a leaky gut impairs metabolic function, which is mediated by chronic low-grade inflammation. ( 29 ) We previously found that mice with leaky guts exhibited glucose intolerance, ( 30 ) which may be involved in low glucose uptake and mitochondrial dysfunction. Under these leaky-gut conditions, muscle fatigue and failure to metabolic adaptation take place easily.…”
Section: Discussionmentioning
confidence: 99%
“…17,89 Aditivi u hrani, uglavnom prehrambeni surfaktanti, imaju štetne toksične učinke na epitelnu barijeru crije va, a emulgator hrane, kao što je Polysorbat-80, po većava propusnost barijere za alergene. 90,91 Maltodek strin, prehrambeni zgušnjivač koji se široko koristi u formulama za dojenčad, izaziva retikularni stres, upalu i deficit mucina na crijevnom epitelu. 91,92 Osim pre hrambenih aditiva, druge komponente iz hrane tako đer mogu oštetiti epitelne barijere.…”
Section: šTetni Učinci Prehrane Na Razvoj Alergijskih Bolestiunclassified